Nursing cooperation of four-handed procedure for apical barrier technique under dental microscope combined with iRoot BP plus (实施显微镜下根尖屏障术联合应用iRoot BP plus的四手操作护理配合及体会) - GE Xin (葛鑫); MA Tao (马涛); WANG Xiaoyan (王晓燕) (中西医结合护理)
Objective To explore the key points of four-handed procedure and nursing cooperation in the application of iRoot BP plus under dental microscope. Methods A total of 108 patients who underwent apical barrier surgery in our hospital from 2018 to 2019 were retrospectively selected. The apical barrier was established using iRoot BP plus under the dental microscope, and the treatment was completed with four-handed procedure. Results The four-handed procedure and related nursing cooperation were smoothly taken. Immediately after operation, X-ray films showed that the filling results reached the standard, and the treatment effect was satisfactory. The treatment time was shortened and work efficiency was improved. Conclusion The apical barrier technique with iRoot BP plus under the dental microscope requires fine, precise operation, and requires high chairside care. High-quality four-handed procedure and nursing cooperation, can improve the overall work efficiency, shorten the treatment time, thus help the doctors to complete the treatment more smoothly. (目的 探究显微镜下联合应用iRoot BP plus实施根尖屏障术的四手操作护理配合要点。方法 回顾医院牙体牙髓科2018年—2019年进行根尖屏障术治疗的患者108例, 均于显微镜下联合使用iRoot BP plus建立根尖屏障, 采用四手操作式护理配合完成治疗。结果 四手操作护理配合过程顺利, 术后即刻X线片显示充填结果均达到标准, 治疗效果满意。椅旁治疗时间明显缩短, 工作效率显著提高。结论 显微镜下联合使用iRoot BP plus建立根尖屏障术治疗难度大, 需要精细、精准的操作, 对椅旁护理要求高。优质的四手操作护理配合, 可以提高整体工作效率、缩短治疗时间, 配合医生更好地完成治疗。)